2007
DOI: 10.1073/pnas.0610503104
|View full text |Cite
|
Sign up to set email alerts
|

The identification of bacillaene, the product of the PksX megacomplex in Bacillus subtilis

Abstract: The Ϸ80-kb pksX gene cluster in Bacillus subtilis encodes an unusual hybrid polyketide/nonribosomal peptide synthase that has been linked to the production of the uncharacterized antibiotic bacillaene. Multiple copies of this synthase, each similar in size to the ribosome, assemble into a single organelle-like complex with a mass of tens to hundreds of megadaltons. The resource requirements of the assembled megacomplex suggest that bacillaene has an important biological role. By coupling a differential NMR spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
232
2
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 247 publications
(241 citation statements)
references
References 19 publications
6
232
2
1
Order By: Relevance
“…Previous experience with identification of novel secondary products in unfractionated microbial extracts suggested that DANS, a method based on overlaying 2D-NMR spectra, could be used to directly detect the daf-22-dependent compounds (17,18). DANS, as shown previously, can provide detailed structural information even for minor components in complex metabolite extracts.…”
Section: Nmr-spectroscopic Comparison Of Wildmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous experience with identification of novel secondary products in unfractionated microbial extracts suggested that DANS, a method based on overlaying 2D-NMR spectra, could be used to directly detect the daf-22-dependent compounds (17,18). DANS, as shown previously, can provide detailed structural information even for minor components in complex metabolite extracts.…”
Section: Nmr-spectroscopic Comparison Of Wildmentioning
confidence: 96%
“…However, the armamentarium of traditional natural product chemistry appears ill-suited for this purpose, given the complexity of metabolomes and the scope of assigning functions to hundreds if not thousands of individual components, many of which represent previously undescribed chemical structures (15). We have developed an NMR-based approach that simplifies linking naturally occurring small molecules with their biological function and offers considerable advantages for the detection of synergism as well as for the characterization of chemically labile signaling molecules (16)(17)(18). Central to our method is the use of genetic information to detect individual compounds in the C. elegans metabolome that could be of interest within a specific biological context.…”
Section: T He Importance Of Small-molecule Signaling In the Biology Ofmentioning
confidence: 99%
“…A recent report has assigned the pks gene cluster to production of bacillaene based on the analysis of an orthologous gene cluster from Bacillus amyloliquefaciens FZB42 called bae (6). In concurrent work, we have solved the structure of bacillaene from B. subtilis and proposed a model for its biosynthesis (28). Bioinformatic analyses of the bacillaene synthase gene cluster reveal features in common with unconventional PKSs from streptomycetes, myxobacteria, and cyanobacteria (see Fig.…”
mentioning
confidence: 95%
“…The hybrid PK/ NRPs dihydrobacillaene and bacillaene are biosignaling agents from Bacillus subtilis where each can be described as a diamide of -amino polyenoic acids that is N-capped with an ␣-hydroxyisocaproate (␣-HIC) moiety (3). The metabolite initially arising from their shared assembly line is dihydrobacillaene, which is later converted to bacillaene by the cytochrome P450 PksS, which oxidizes the saturated C14Ј-C15Ј bond of dihydrobacillaene to an olefin (3)(4)(5).…”
mentioning
confidence: 99%
“…The hybrid PK/ NRPs dihydrobacillaene and bacillaene are biosignaling agents from Bacillus subtilis where each can be described as a diamide of -amino polyenoic acids that is N-capped with an ␣-hydroxyisocaproate (␣-HIC) moiety (3). The metabolite initially arising from their shared assembly line is dihydrobacillaene, which is later converted to bacillaene by the cytochrome P450 PksS, which oxidizes the saturated C14Ј-C15Ј bond of dihydrobacillaene to an olefin (3)(4)(5). Previous work has shown the dihydrobacillaene assembly line to be a rich source of unusual biochemistry, where hybrid PK synthase (PKS)/NRP synthetase assembly-line proteins are used in conjunction with enzyme machinery borrowed from both isoprenoid and polyunsaturated fatty acid biosynthesis (6).…”
mentioning
confidence: 99%